2019
DOI: 10.1002/pon.5225
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in barriers to symptomatic presentation in primary care: A survey of women in England

Abstract: Objective The majority of cancers are diagnosed following a decision to access medical help for symptoms. People from ethnic minority backgrounds have longer patient intervals following identification of cancer symptoms. This study quantified ethnic differences in barriers to symptomatic presentation including culturally specific barriers. Correlates of barriers (eg, migration status, health literacy, and fatalism) were also explored. Methods A cross‐sectional survey of 720 White British, Caribbean, African, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“… 17 Other studies have suggested a connection between ethnic group and fatalism, and, for some groups, body vigilance. 18 , 19 Furthermore, if the patient’s preferred language is not the same as the GP’s, difficulties in explaining symptoms or a gut feeling, which is difficult to describe even in the informant’s native language, 2 may harm the development and use of gut feeling. As such, it is conceivable that ethnic background may influence the GP’s use of the ‘short cut’ to investigations that gut feelings provide, the patients’ experience of being taken seriously by their GP, and their views on gut feelings, but this is beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 17 Other studies have suggested a connection between ethnic group and fatalism, and, for some groups, body vigilance. 18 , 19 Furthermore, if the patient’s preferred language is not the same as the GP’s, difficulties in explaining symptoms or a gut feeling, which is difficult to describe even in the informant’s native language, 2 may harm the development and use of gut feeling. As such, it is conceivable that ethnic background may influence the GP’s use of the ‘short cut’ to investigations that gut feelings provide, the patients’ experience of being taken seriously by their GP, and their views on gut feelings, but this is beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 99%
“…While no research has examined how ethnicity may affect the expression or use of gut-feelings for serious illness either from the perspective of the patient or the GP, a patient's ethnicity has been associated with increased consultations, with patients of Black, Asian, and Mixed ethnicity having a greater chance of attending their GP three or more times before hospital referral than White patients (17). Other studies have suggested a connection between ethnic group and fatalism and, for some groups, body vigilance (18,19). Furthermore, if the patient's preferred language is not the same as the GP's difficulties in explaining symptoms or a gut-feeling, which is difficult to describe even in the informant's native language (2), may harm the development and use of gut-feeling.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Specialist post-COVID-19 clinics for support from multidisciplinary teams and individualised rehabilitation plans are accessed via primary care services [25]. Minority groups may experience additional barriers to accessing support for their symptoms, such as, lack of trust in professionals, feelings of embarrassment and fear, fatalistic beliefs (shaped by religion/culture) and alternative understandings of causes, symptoms and treatments, lower language proficiency, not presenting to healthcare for certain symptoms and not having culturally-relevant terms to describe medicalised conditions or terms [26][27][28][29][30][31][32][33][34].…”
Section: Plos Onementioning
confidence: 99%
“…In order for an event to occur, the patient must first seek medical care. The extent to which care is sought for symptoms varies not only by symptom knowledge, interpretation, and beliefs (Petrova et al, 2019), but also by ethnicity (Williams et al, 2019), socioeconomic status (McCutchan et al, 2015, and gender (Magaard et al, 2017). Second, the presence or absence of an event is subject to the clinical judgment of a provider.…”
Section: Stage 1 (Event Occurs)mentioning
confidence: 99%